# Ordinary Differential Equations Questions and Answers – Special Functions – 4 (Legendre)

«
»

This set of Ordinary Differential Equations Questions and Answers for Campus interviews focuses on “Special Functions – 4 (Legendre)”.

1. Find the General Solution of the given differential equation.
$$(8x+7)\frac{dy}{dx}+2y=x$$
a) $$c_1(\frac{1}{(8x+7)})^\frac{1}{4}+\frac{(8x+7)}{40}-\frac{5}{16}$$
b) $$c_1(\frac{1}{(8x+7)})^\frac{1}{4}+\frac{(8x+7)}{80}-\frac{7}{8}$$
c) $$c_1(\frac{1}{(8x+7)})^\frac{1}{4}+\frac{(8x+7)}{40}-\frac{7}{16}$$
d) $$c_1(\frac{1}{(8x+7)})^\frac{1}{4}+\frac{(8x+7)}{80}-\frac{7}{16}$$

Explanation: This special case where D has a co-efficient is solved using Legendre’s method.
Let log⁡(8x+7)=z
Then, ez=8x+7
$$(8x+7)\frac{dy}{dx}=8Dy$$, where D=$$\frac{d}{dz}$$
Substituting this in the equation,
8Dy+2y=x
y(8D+2)=x
Thus the auxiliary equation is 8D+2=0
Thus, D = $$\frac{-1}{4}$$
C.F = $$c_1 e^{\frac{-z}{4}} = c_1(\frac{1}{(8x+7)})^\frac{1}{4}$$
P.I = $$\frac{1}{(8D+2)} × x$$
= $$\frac{1}{(8D+2)} × (\frac{e^z-7}{8})$$
= $$\frac{1}{(8D+2)} × \frac{e^z}{8} – \frac{1}{(8D+2)} × \frac{7}{8} × e^0$$(Solving by substituting powers of ez)
= $$\frac{e^z}{80}-\frac{7}{16}$$
=$$\frac{(8x+7)}{80}-\frac{7}{16}$$
The General solution is C.F+P.I = $$c_1(\frac{1}{(8x+7)})^\frac{1}{4}+\frac{(8x+7)}{80}-\frac{7}{16}.$$

2. Find the Continuous Function and Particular Integral for the given differential equation.
$$(2x+3)\frac{dy}{dx}-3y=8x$$
a) $$c_1(2x+3)^\frac{5}{2}, -4(2x+3)-4$$
b) $$c_1(2x+3)^\frac{3}{2}, -2(2x+3)-4$$
c) $$c_1(2x+3)^\frac{3}{2}, -4(2x+3)-4$$
d) $$c_1(2x+3)^\frac{3}{2}, -4(2x+3)-4$$

Explanation: This is the special case of Legendre’s Function.
Assume log(2x+3)=z
Then, ez=2x+3
$$(2x+3)\frac{dy}{dx}=2Dy$$, where D=$$\frac{d}{dz}$$
Substituting this in the equation,
2Dy-3y=8x
y(2D-3)=8x
Thus the auxiliary equation is 2D-3=0
Thus, D=$$\frac{3}{2}$$
C.F=$$c_1 e^\frac{3z}{2} = c_1(2x+3)^\frac{3}{2}$$
P.I=$$\frac{1}{(2D-3)}×8x$$
=$$\frac{1}{(2D-3)}×8(\frac{e^z-3}{2})$$
=$$\frac{1}{(2D-3)}×e^\frac{z}{2}×8-\frac{1}{(2D-3)}×8×\frac{-3}{2}×e^0$$ (Solving by substituting powers of ez)
=-4ez-4
=-4(2x+3)-4
Thus, C.F is $$c_1(2x+3)^\frac{3}{2}$$
And P.I is -4(2x+3)-4.

3. Find the C.F of the following Differential Equation.
$$(2x+3)^2 \frac{d^2 y}{dx^2} + (2x+3)\frac{dy}{dx} – 2y = x$$
a) $$c_1(2x+3)+ c_2(2x+3)^\frac{-1}{2}$$
b) $$c_1(2x+3)+ c_2(2x+3)^\frac{1}{2}$$
c) $$c_1(2x+3)+ c_2(2x+3)^\frac{-3}{2}$$
d) $$c_1(2x+3)+ c_2(2x+3)^\frac{-1}{2}$$

Explanation: Assume log⁡(2x+3)=z
Then, ez=(2x+3)
(2x+3)$$\frac{dy}{dx}$$=2Dy, Where D is $$\frac{d}{dz}$$
$$(2x+3)^2 \frac{d^2 y}{dx^2}=2^2 D(D-1)y$$
Substituting in the equation given
4D(D-1)y+2Dy-2y=x
y(4D(D-1)+2D-2)=x
y(4D2-2D-2)=x
Thus, the Auxiliary Equation is 4D2-2D-2
D=1 or D=$$\frac{-1}{2}$$
Thus, the C.F for the given equation is $$c_1e^z + c_2e^\frac{-z}{2}=c_1(2x+3) + c_2(2x+3)^\frac{-1}{2}$$.

4. Find the P.I of the given Differential Equation.
$$(x+1)^2 \frac{d^2 y}{dx^2}+(x+1) \frac{dy}{dx}+y=sin⁡(log⁡(1+x))$$
a) -log⁡(x+1)×$$\frac{cos⁡(log⁡(x+1))}{2}$$
b) -log⁡(x+1)×$$\frac{sin⁡(log⁡(x+1))}{2}$$
c) log⁡(x+1)×$$\frac{cos⁡(log⁡(x+1))}{2}$$
d) -log⁡(x+2)×$$\frac{cos⁡(log⁡(x+1))}{2}$$

Explanation: Assume log⁡(x+1)=z
Then, ez=(x+1)
$$(x+1)\frac{dy}{dx}=Dy$$, Where D is $$\frac{d}{dz}$$
$$(x+1)^2 \frac{d^2 y}{dx^2}=D(D-1)y$$
Substituting in the equation given
D(D-1)y+Dy+y = sin⁡(log⁡(1+x))
y(D(D-1)+D+1) = sin⁡(log⁡(1+x))
y(D2+1) = sin⁡(log⁡(1+x))
Thus, the Auxiliary Equation is D2+1
P.I = $$\frac{1}{D^2+1}$$×sin⁡(z)
To find P.I, substitute D2=-(1)2
Since the denominator becomes zero, multiply the numerator by z and differentiate the denominator.
P.I = $$\frac{z}{2D}$$×sin⁡(z)
=$$\frac{-zcos(z)}{2}$$
=-log⁡(x+1)×$$\frac{cos⁡(log⁡(x+1))}{2}$$.

5. Solve this Differential Equation to find its General Solution.
$$(x+3)\frac{d^2y}{dx^2}+2 \frac{dy}{dx}+\frac{y}{(x+3)}=4$$
a) $$\frac{4x}{3}+2+\frac{1}{(x+3)}×c_1cos⁡(\frac{\sqrt{3}}{2} log⁡(x+3))+c_2sin⁡(\frac{\sqrt{3}}{2} log⁡(x+3))$$
b) $$\frac{4x}{3}+4+\frac{1}{(x+3)}×c_1cos⁡(\frac{\sqrt{3}}{2} log⁡(x+3))+c_2sin⁡(\frac{\sqrt{3}}{2} log⁡(x+3))$$
c) $$x+4+\frac{1}{(x+3)}×c_1cos⁡(\frac{\sqrt{3}}{2} log⁡(x+3))+c_2sin⁡(\frac{\sqrt{3}}{2} log⁡(x+3))$$
d) $$\frac{2x}{3}+4+\frac{1}{(x+3)}×c_1cos⁡(\frac{\sqrt{3}}{2} log⁡(x+3))+c_2sin⁡(\frac{\sqrt{3}}{2} log⁡(x+3))$$

Explanation: Multiply both the sides with (x+3)
We get the equation,
$$(x+3)^2 \frac{d^2 y}{dx^2}+2(x+3) \frac{dy}{dx}+y=4(x+3)$$
This equation is in Legendre’s form.
Assume log⁡(x+3)=z
Then, ez=(x+3)
$$(x+3)\frac{dy}{dx}=Dy$$, Where D is $$\frac{d}{dz}$$
$$(x+3)^2 \frac{d^2 y}{dx^2}=D(D-1)y$$
Substituting in the equation given
D(D-1)y+2Dy+y=4(x+3)
y(D(D-1)+2D+1)=4(x+3)
y(D2+D+1)=4(x+3)
Thus, the Auxiliary Equation is D2+D+1=0
$$D=\frac{-1}{2}+\frac{\sqrt{3}}{2}i \,or\. D=\frac{-1}{2}-\frac{\sqrt{3}}{2}i$$
Thus, the C.F for the given equation is $$e^{\frac{-z}{2}} (c_1cos⁡(\frac{\sqrt{3}}{2}z)+c_2sin⁡(\frac{\sqrt{3}}{2}z))$$
C.F = $$\frac{1}{(x+3)}× c_1cos⁡(\frac{\sqrt{3}}{2} log⁡(x+3))+c_2sin⁡(\frac{\sqrt{3}}{2} log⁡(x+3))$$
P.I = $$\frac{1}{D^2+D+1}×4e^z$$
To find P.I, substitute D=1
P.I = $$\frac{4×e^z}{3}$$
= $$\frac{4×(x+3)}{3}$$
= $$\frac{4x}{3}+4$$
Thus, the general solution is
$$\frac{1}{(x+3)}× c_1cos⁡(\frac{\sqrt{3}}{2} log⁡(x+3))+c_2sin⁡(\frac{\sqrt{3}}{2} log⁡(x+3))+\frac{4x}{3}+4$$
.

6. Find the C.F for the following Differential Equation.
$$(3x+2)^3 \frac{d^3y}{dx^3}+2(3x+2)^2 \frac{d^2 y}{dx^2}+(3x+2) \frac{dy}{dx}-y=(3x+2)^2$$
a) $$c_1(3x+2)^{0.022}+(3x+2)^{1.15}(c_2 cos⁡(0.22 log⁡(3x+2))+c_3 sin(0.22 log⁡(3x+2)))$$
b) $$c_1(3x+2)^{0.022}+(3x+2)^{1.15}(c_2 cos⁡(0.22 log⁡(3x+3))+c_3 sin(0.22 log⁡(3x+2)))$$
c) $$c_1(3x+2)^{0.026}+(3x+2)^{1.15}(c_2 cos⁡(0.22 log⁡(3x+2))+c_3 sin(0.22 log⁡(3x+2)))$$
d) $$c_1(3x+2)^{0.022}+(3x+2)^{1.15}(c_2 sin⁡(0.22 log⁡(3x+2))+c_3 sin(0.22 log⁡(3x+2)))$$

Explanation: This equation is in the Legendre Form.
Assume log⁡(3x+2)=z
Then, ez=(3x+2)
$$(3x+2) \frac{dy}{dx}=3Dy$$, Where D is $$\frac{d}{dz}$$
$$(3x+2)^2 \frac{d^2 y}{dx^2}=3^2 D(D-1)y$$
$$(3x+2)^3 \frac{d^3 y}{dx^3}=3^3 D(D-1)(D-2)y$$

Substituting in the equation given

27D(D-1)(D-2)y+18D(D-1)y+3Dy-y=(3x+2)2
y(27(D(D-1)(D-2))+18(D(D-1))+3D-1)=(3x+2)2
y(27D3-63D2+39D-1)
Thus the Auxiliary Equation is 27D3-63D2+39D-1=0
D=0.026 or D=1.15+0.22i or D=1.15-0.22i

Thus, the C.F of the equation is given by
C.F=$$c_1e^{0.026z}+e^{1.15z} (c_2cos⁡(0.22z)+c_3sin(0.22z))$$
C.F=$$c_1(3x+2)^{0.026}+(3x+2)^{1.15} (c_2cos⁡(0.22 log⁡(3x+2))+c_3sin(0.22 log⁡(3x+2)))$$.

7. Find the solution for the given Higher Order Differential Equation.
$$2(3x+5)^2 \frac{d^2 y}{dx^2}+(3x+5) \frac{dy}{dx}+y=sin⁡(log⁡(3x+5))$$
a) $$c_1(3x+5)^{0.76}+ c_2(3x+5)^{0.073}+\frac{-(15(cos⁡(log⁡(3x+5))+17 sin⁡(log⁡(3x+5)))))}{64}$$
b) $$c_1(3x+5)^{0.76}+ c_2(3x+7)^{0.073}+\frac{-(15(cos⁡(log⁡(3x+5))+17 sin⁡(log⁡(3x+5)))))}{64}$$
c) $$c_1(3x+5)^{0.76}+ c_2(3x+7)^{0.073}+\frac{-(15(cos⁡(log⁡(3x+5))+17 sin⁡(log⁡(3x+5)))))}{16}$$
d) $$c_1(3x+5)^{0.76}+ c_2(3x+5)^{0.073}+\frac{-(15(cos⁡(log⁡(3x+5))+17 sin⁡(log⁡(3x+5)))))}{16}$$

Explanation: The given equation is a Legendre’s Function.
Assume log⁡(3x+5)=z
Then, ez=(3x+5)
$$(3x+5) \frac{dy}{dx}=3Dy$$, Where D is $$\frac{d}{dz}$$
$$(3x+5)^2 \frac{d^2 y}{dx^2}=3^2 D(D-1)y$$
Substituting in the equation given
(2×9)D(D-1)y+3Dy+y= sin⁡(log⁡(1+x))
y(18(D2-D)+3D+1) = sin⁡(log⁡(1+x))
y(18D2-15D+1) = sin⁡(log⁡(1+x))
Thus, the Auxiliary Equation is 18D2-15D+1
D=0.76 or D=-0.073
Thus, the C.F for the given equation is
$$c_1e^{0.76}z+ c_2e^{0.073}z=c_1(3x+5)^{0.76}+ c_2(3x+5)^{0.073}$$
P.I = $$\frac{1}{(18D^2-15D+1)}×sin⁡(z)$$
To find P.I, substitute D2=-(1)2
=$$\frac{1}{(-17-15D)}×sin⁡(z)$$
Multiplying numerator and Denominator with factor(17-15D)
=$$\frac{(-15D+17)}{64}×sin⁡(z)$$, Using a2-b2=(a+b)(a-b) and substituting D2=-(1)2
=$$(15(-cos⁡(z)-17 sin⁡(z)))/64$$
=$$\frac{-(15(cos⁡(log⁡(3x+5))+17 sin⁡(log⁡(3x+5)))))}{64}$$
Thus, the general solution is
$$c_1(3x+5)^{0.76}+ c_2(3x+5)^{0.073}+\frac{-(15(cos⁡(log⁡(3x+5))+17 sin⁡(log⁡(3x+5)))))}{64}$$
.

8. Find the C.F for the given Higher Order Differential Equation.
$$x^2 \frac{d^2 y}{dx^2}+3(x+2) \frac{dy}{dx}+4(1+x) \frac{d^2 y}{dx^2}+2y=x$$
a) $$\frac{1}{(x+1)}×(c_1cos⁡(log⁡(x+2))+c_2sin⁡(log⁡(x+2)))$$
b) $$\frac{1}{(x+2)}×(c_1cos⁡(log⁡(x+2))+c_2cos⁡(log⁡(x+2)))$$
c) $$\frac{1}{(x+1)}×(c_1cos⁡(log⁡(x+1))+c_2sin⁡(log⁡(x+1)))$$
d) $$\frac{1}{(x+2)}×(c_1cos⁡(log⁡(x+2))+c_2sin⁡(log⁡(x+2)))$$

Explanation: Bring all terms of $$\frac{d^2 y}{dx^2}$$ together.
$$(x+2)^2 \frac{d^2 y}{dx^2}+3(x+2) \frac{dy}{dx}+2y=x$$
This is in Legendre’s Form.
Let, log⁡(x+2)=z
Then, ez=(x+2)
$$(x+2) \frac{dy}{dx}=Dy$$, Where D is $$\frac{d}{dz}$$
$$(x+2)^2 \frac{d^2 y}{dx^2}=D(D-1)y$$
Substituting in the equation given
D(D-1)y+3Dy+2y=x
y((D2-D)+3D+2)=x
y(D2+D+2)=x
Thus, the Auxiliary Equation is y(D2+D+2)=0
D=-1+i or D=-1-i
C.F is
$$e^{-z}(c_1cos⁡(z)+c_2sin⁡(z))=\frac{1}{(x+2)}×(c_1cos⁡(log⁡(x+2))+c_2sin⁡(log⁡(x+2)))$$.

9. Find the P.I for the given Differential Equation.
$$16x^2 \frac{d^2 y}{dx^2}+(2x+4) \frac{dy}{dx}+4x(x+4) \frac{d^2 y}{dx^2}+2y=cos⁡(log⁡(2x+4))$$
a) $$\frac{1}{4}×(-sin⁡(log⁡(2x+4))+cos⁡(log⁡(2x+4)))$$
b) $$\frac{1}{4}×(-sin⁡(log⁡(2x+4))-cos⁡(log⁡(2x+4)))$$
c) $$\frac{1}{2}×(-sin⁡(log⁡(2x+4))-cos⁡(log⁡(2x+4)))$$
d) $$\frac{1}{2}×(-sin⁡(log⁡(2x+4))+cos⁡(log⁡(2x+4)))$$

Explanation: Bring all terms of $$\frac{d^2 y}{ dx^2}$$ together.
The equation becomes-
$$(2x+4)^2 \frac{d^2 y}{dx^2}+(2x+4) \frac{dy}{dx}+2y= cos⁡(log⁡(2x+4))$$
This is in Legendre’s Form.
Let, log⁡(2x+4)=z
Then, ez=(2x+4)
$$(2x+4) \frac{dy}{dx}=2Dy$$, Where D is $$\frac{d}{dz}$$
$$(2x+4)^2 \frac{d^2 y}{dx^2}=4D(D-1)y$$
Substituting in the equation given
4D(D-1)y+2Dy+2y=cos⁡(log⁡(2x+4))
y(4(D2-D)+2D+2)=cos⁡(log⁡(2x+4))
y(4D2-2D+2)=cos⁡(log⁡(2x+4))
Thus, the Auxiliary Equation is y(4D2-2D+2)=0
P.I = $$\frac{1}{4D^2-2D+2}×cos⁡(log⁡(2x+4))$$
= $$\frac{1}{4D^2-2D+2}×cos⁡(z)$$
In case of cos⁡() function, Substitute D2=-(1)2
= $$\frac{1}{-2-2D}×cos⁡(z)=\frac{-1}{2}×\frac{1}{(D+1)}×cos⁡(z)$$
Multiplying numerator and Denominator with factor(D-1)
=$$\frac{1}{4}×(D-1)×cos⁡(z)$$
=$$\frac{1}{4}×(-sin⁡(z)-cos⁡(z))$$
=$$\frac{1}{4}×(-sin⁡(log⁡(2x+4))-cos⁡(log⁡(2x+4)))$$
Thus, the P.I for the given equation is =$$\frac{1}{4}×(-sin⁡(log⁡(2x+4))-cos⁡(log⁡(2x+4)))$$.

Sanfoundry Global Education & Learning Series – Ordinary Differential Equations.

To practice all areas of Ordinary Differential Equations for Campus Interviews, here is complete set of 1000+ Multiple Choice Questions and Answers.

Participate in the Sanfoundry Certification contest to get free Certificate of Merit. Join our social networks below and stay updated with latest contests, videos, internships and jobs! 